Epidemiology of oesophageal stricture and its outcome: a study among patients attending a tertiary hospital of Kolkata - Subrata Dey; Indira Dey; Bhaskar Das; Dipayan Ghosh (Al Ameen Medical College, 2013)
Background: Corrosive ingestion is a common cause of upper gastro intestinal tract injury globally and in India as well. It is often used as a suicidal and homicidal agent although accidental ingestion are also common. Objectives: In this study an endeavor was made to study the socio-demographic profile and etiology of oesophageal stricture cases, to assess the long term effects of corrosive poisoning and to formulate an effective therapeutic protocol to treat the cases. Methodology: A prospective study was carried out among patients with history of corrosive ingestion attending the OPD of Department of Cardiovascular and Thoracic Surgery of a tertiary medical college of Kolkata from Jan to December, 2009. A pretested and predesigned schedule was used for data collection. Result: The present study revealed that 81.53% of the patients were female and 87.7% of the patients ingested corrosives to commit suicide. Only 13.8% were given water as pre hospital treatment and almost all the patients were taken to the health facility within 2 to 5 hours. Regular dilatation and operative procedures like gastrojejunostomy and colon bypass were found to be safe and effective in improving the swallowing function. There was no mortality among the cases. Conclusion: Ingestion of corrosives appear to be common in this part and approaches may include increasing peoples' skill in coping with problems by providing coping skill classes at school and counseling in the community.